2015
DOI: 10.2118/2014-1922521-pa
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Based Characterization of Calcite-Filled Fractures and Porosity in Shales

Abstract: Gas-and liquid-rich shales exhibit structural and compositional features across a broad range of length scales from meters to nanometers. This laboratory characterization effort of a shale sample aids hydrocarbon resource and reserves estimation, and improves understanding of flow behavior including potential geological carbon dioxide storage. Multiscale laboratory-imaging techniques were applied to characterize pore and microfracture structure of a Barnett Shale sample including connectivity and heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Fractures can be imaged using OM/SEM (Gale et al 2014;Gasparrini et al 2014) and XCT in 2D and 3D respectively (Kobchenko et al 2011;Vega et al 2014;Carey et al 2015) (Figure 8 a-b). SEM (Chalmers et al 2012;Wu and Aguilera 2012;Vega et al 2014) and 3D-EM (Torsaeter et al 2012;Chen et al 2015) are commonly used for micro-scale imaging of fractures. Where fractures are cement-filled, combining optical microscopy with SEM imaging can provide mineralogical and microstrucutre information.…”
Section: Fracturesmentioning
confidence: 99%
See 3 more Smart Citations
“…Fractures can be imaged using OM/SEM (Gale et al 2014;Gasparrini et al 2014) and XCT in 2D and 3D respectively (Kobchenko et al 2011;Vega et al 2014;Carey et al 2015) (Figure 8 a-b). SEM (Chalmers et al 2012;Wu and Aguilera 2012;Vega et al 2014) and 3D-EM (Torsaeter et al 2012;Chen et al 2015) are commonly used for micro-scale imaging of fractures. Where fractures are cement-filled, combining optical microscopy with SEM imaging can provide mineralogical and microstrucutre information.…”
Section: Fracturesmentioning
confidence: 99%
“…Where fractures are cement-filled, combining optical microscopy with SEM imaging can provide mineralogical and microstrucutre information. Some scholars (Vega et al 2014;Ma 2016) have demonstrated the connectivities and heterogeneity of fractures and their distribution with minerals by using XCT (Figure 8 c). Recently, XCT is used for fracture characterisation because the sample can be imaged internally and also because image processing techniques enables the quantification and spatial distribution of shale components.…”
Section: Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Shale gas formations have heterogeneous mineralogy and structure (Vega et al, ). The rocks are characterized by extremely low permeability, low porosity, nanometer‐scale pore sizes, and high organic matter content (Chalmers et al, ; Clarkson et al, ).…”
Section: Introduction To the Shale Gas Systemmentioning
confidence: 99%